An evaluation of the Victorian Salt Reduction Partnership's advocacy strategy for policy change - Emalie Rosewarne; Michael Moore; Wai-Kwan Chislett; Alexandra Jones; Kathy Trieu; Jacqui Webster (BMC, 2021)
Abstract Background Public health advocacy strategies facilitate policy change by bringing key health issues to the forefront of public and political discourse, influencing decision-makers and public opinion, and increasing policy demand. The Victorian Salt Reduction Partnership (VSRP) was established in 2014 in response to inadequate government action to improve population diets in Australia. This study aimed to evaluate the success of the VSRP's advocacy strategy in achieving policy change. Methods Documentation of VSRP activities and outputs were collected, and semi-structured interviews conducted as part of a comprehensive process evaluation. For this study, the Kotter Plus 10-step public health advocacy evaluation framework was used to guide data extraction, analysis, and synthesis. Results A sense of urgency for salt reduction was generated by producing evidence and outlining the potential impact of a state-based salt reduction programme. This enabled the creation of a coalition with diverse skills and expertise, which facilitated the development of an innovative and collaborative advocacy action plan. A clear change vision was established, but communication of the vision to decision-makers was lacking, which reduced the impact of the programme as decision-makers were not provided with a clear incentive for policy change. As a result, while programme outputs were achieved, these did not translate to achieving broader strategic goals during a limited-term intervention in a political climate unconcerned with salt. Conclusions The Kotter Plus 10-step framework was a useful tool for evaluating the success of the VSRP advocacy strategy. The framework enabled the identification of key strengths, including the creation of the guiding coalition, and areas where efforts could be improved in future similar strategies, such as effective communication within partnerships and to decision-makers, to better influence policy and improve public health impact.